Study of bacterial contamination for sterile eye drops (Journal of the College of Basic Education, 2022)
Collected 24 samples of sterile eye drops from pharmacies in Baghdad and studied microbial content drops, and the results showed the presence of bacteria positive and negative gram stain in some samples, as observed high percentage of bacteria Staphylococcus .albus 62% either bacteria klbsiella spp 25% and E. coli, 13%, while the effectiveness of the drops in the inhibition of the growth of the bacteria E.coli and S. aureus as the use of well diffusion method , results showed the samples 3, 4, 7, 9, 15 and 16 did not give any inhibition while samples 2, 11, 12 and 14 is observed given the high inhibition up to 52mm as in the sample 2. The inhibition against S.aureu as noted there was significant different between positive and negative bacteria as it gave samples 2, 5, 10, 11, 12 and 14, the highest inhibition up to 60 mm, while samples 4 and 16 did not give any percentage of inhibition, either study the effect of storage on contamination ant inhabition activity of samples (17-24), the results showed that the samples are stored for 21 days and sample 21 showed contamination after 14 days of storage, while observed contamination of samples 17, 19 and 20 on the first day of the opening is not observed an increase in pollution length of the storage period. The samples 18, 22, 23 and 24 have not observed contamination along the storage period. When examining the activity of the drops in the inhibition of positive and negative bacteria ,observed don’t decrease in the activity of the inhibition of the samples consistently storage period period.